A Glimpse into the Past and a Look Towards the Future with Artificial Intelligence - Mehdi Mortazavi (Iranian Journal of Archaeological Studies, 2023)
The Iranian Journal of Archaeological Studies, volume 13, number 2, year 2023 welcomes you! Explore a variety of archaeological landscapes from the Palaeolithic to the modern era as we go on an intriguing voyage through time and space in this issue.